History Teacher Perceptions of the Implementation of Merdeka Belajar Curriculum at SMAS Kemala Bhayangkari 1 Kubu Raya - Riski, Herlin Purnika; Chalimi, Ika Rahmatika (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The purpose of the study was to collect data regarding teachers' perceptions of the curriculum for first-year students at SMAS Kemala Bhayangkari 1 Kubu Raya using qualitative descriptive methods. Data were obtained by conducting observations, interviews, and documentation with subject matter experts and the curriculum team. Data analysis was conducted using data reduction, data entry, and data validation techniques.  The research findings highlight teachers' perceptions of the Merdeka Belajar curriculum, which is different from the 2013 curriculum. History subjects in the independent learning curriculum are a combination of specialization and compulsory history. In addition, in phase E or grade X, history subjects are combined with other subjects such as sociology, economics, and geography into social studies. However, in phase F or grades XI and XII history subjects are independent. In the implementation of an independent learning curriculum, history teachers must be able to combine various methods and models as well as the use of technology to produce fun and independent learning in accordance with the profile of Pancasila students.